Implementation and outcome of child psychotherapy compared with other psychiatric treatments in a naturalistic clinical setting. (April 2015) - Ryynänen, Taimi; Alen, Markku; Koivumaa-Honkanen, Heli; Joskitt, Leena; Ebeling, Hanna
Abstract: Background: Mental health problems of children are commonly treated by psychotherapy and other psychosocial treatments. Studies comparing different treatments in naturalistic clinical settings are few, however. Aims: We assessed the differences: 1) in symptoms and diagnoses; 2) in treatment outcome between psychotherapy and other psychosocial treatments; and 3) evaluated the effect of family background and life circumstances on the outcome. Methods: The data were collected from the psychiatric hospital records of Oulu University Hospital, Finland. All 118 children (aged < 16 years) referred to psychotherapy from the Department of Child Psychiatry in 1996–2005 and 118 age- and sex-matched children undergoing other psychosocial treatments were included. A lack of later recorded psychiatric problems was used as an indicator of good treatment outcome. Results: On referral, functional ability was severely impaired in almost half of the children (Children's Global Assessment Scale score < 55). Internalizing symptoms were more common in the psychotherapy group, while no difference was found in externalizing symptoms between the groups. In both groups, later psychiatric problems were associated with a child's low functional ability and poor parental coping with their responsibilities. Children with internalizing problems had impaired prognosis if they had psychosocial treatments other than psychotherapy. Conclusions: Individual psychotherapy should especially be considered for children with internalizing symptoms, but the outcome of psychiatric treatment depends not only on children's own functional abilities, but also on parental abilities.